2004
DOI: 10.1191/0267659104pf764oa
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular assist device thrombosis during biventricular heart assistance

Abstract: We report a case of total thrombosis of a right ventricular assist device in a patient during biventricular assistance. The thrombosis occurred 18 days following implantation and the right ventricular device was immediately removed without any complications. The patient was successfully transplanted after 3 months of left ventricular assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In clinical terms, where PVR has a reference range of 155 to 255 dyne/s/cm 5 , a conduit of 40 cm should always function within the manufacturer's guidelines based on our in vitro results. This is important, as low flow through devices have been reported as contributory factors to intrapump thrombosis , while higher than recommended speeds result in excessive power consumption. We note that a variation in banding diameter may achieve a similar outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical terms, where PVR has a reference range of 155 to 255 dyne/s/cm 5 , a conduit of 40 cm should always function within the manufacturer's guidelines based on our in vitro results. This is important, as low flow through devices have been reported as contributory factors to intrapump thrombosis , while higher than recommended speeds result in excessive power consumption. We note that a variation in banding diameter may achieve a similar outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Most often, fibrin or thrombus formation in the VAD is generated near the inflow or outflow valve or in the pump chamber as the result of insufficient anticoagulation or a poorly adjusted system. 12,13 In addition, particular flow characteristics inside the VAD, such as vortex formation, flow reversal, and thus increased residence times, may explain the high rate of thromboembolic events after VAD implantation and the described changes in von Willebrand factor. 13 A number of studies based on different imaging modalities (ultrasound, particle imaging velocimetry [PIV]) or numeric simulations (computational fluid dynamics) have investigated flow patterns inside assist devices.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of different operating conditions, often observed in the clinical routine (optimal vs suboptimal driving of the device), on regional flow characteristics, and thus risk for thrombus formation, is poorly understood. 12,13,18 The purpose of this study was to use flow-sensitive 4D MRI for a detailed analysis of 3D flow dynamics and function of the inlet and outlet valve systems in a clinical routine VAD for different system adjustments representing optimal and impaired operating conditions. In a second set of experiments, the effect of different valve designs on regional flow patterns and valve dynamics were directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…Right atrial cannulation is an obvious alternative method for placement of the inflow cannula of the RVAD. However, thrombosis inside the right atrial inflow cannula can pose a serious complication for chronic RVAD support (10). Our recent animal study (11) showed that the DexAide RVAD with the inflow cannula inserted through the diaphragmatic surface of the right ventricle demonstrates good biocompatibility.…”
Section: Discussionmentioning
confidence: 99%